2020
DOI: 10.17509/jsl.v3i3.21906
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality in Science Education: a Descriptive Review

Abstract: The term “Virtual Reality” currently refers to a profound sensory immersion of the user in a synthetically generated virtual environment. It is foreseen that virtual reality will gain a substantial role in the instruction of science. In this literature review, the purpose was to investigate the research on the utilization of virtual reality in the science education context, according to several criteria. The articles published in peer-reviewed journals and academic conferences/symposiums that are available in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
4
14
1
4
Order By: Relevance
“…Focusing on the use of virtual reality technologies in science education, Durukan et al (2020) conducted a study to review literature on the use of virtual reality technologies in science education based on some criteria that include: publication type, country origin, research design, sample or participants, investigated variables and situations. For the purpose of the study, 30 research papers were selected for the review.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Focusing on the use of virtual reality technologies in science education, Durukan et al (2020) conducted a study to review literature on the use of virtual reality technologies in science education based on some criteria that include: publication type, country origin, research design, sample or participants, investigated variables and situations. For the purpose of the study, 30 research papers were selected for the review.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Durukan, Artun, and Temur (2020) examined the types of research methods in the papers that examined the applications of VR technologies in science education. They found that out of the 30 research studies, half of them (50%) were experimental studies, and about a quarter (27%) of the examined studies were classified as descriptive in terms of introducing possible results and existing chances associated with the use of VR technologies in education.…”
Section: The Distribution Of Studies That Investigated the Applicatio...mentioning
confidence: 99%
“…These sources include different types of students, teachers, and previous studies (Luo, et al, 2021). Durukan, Artun, and Temur (2020) examined the distribution of sample or data sources of the reviewed studies that investigate the applications of VR technologies in science education. They found that out of the 30 research studies, 27% of them collected data from undergraduate students who were in different majors.…”
Section: The Distribution Of Studies That Investigated the Applicatio...mentioning
confidence: 99%
“…ese studies reviewed the previous articles to answer specific research questions for understanding important keywords or topics of the field. Some review papers focused on the trends of virtual reality-based education research related to specific fields as shown in Table 1, such as Earth science engineering education [7], medical education [8,19], STEM education [20], math education [21], computer science education [22], higher education [23][24][25], heritage education [26], rehabilitation management of breast cancer survivors [27], virtual reality-based training for daily living in patients with chronic stroke [28], PSTD treatments [29], foreign language learning gamification using virtual reality [30,31], K-12 and higher education [15,17], surgical training [32], industrial skills training [31], virtual reality cognitive training in individuals with mild cognitive impairment [16,18], science education [33,34], sensorimotor learning [35], dental education [36], virtual reality-based emotional response and symptom provocation in patients with OCD (obsessive compulsive disorder) [37], nursing education [38,39], virtual reality therapy for social anxiety disorder [40], evacuation training [41], virtual reality-assisted neuromuscular therapy [42], home-based virtual reality rehabilitation for individuals with Parkinson disease [43], virtual realitybased physiology and anatomy learning [44], social work education [45], and marketing higher education …”
Section: Introductionmentioning
confidence: 99%